Tabungan Emas sebagai Instrumen Perencanaan Keuangan Ibadah Haji: Studi Kasus Bank Syariah Indonesia - Setiawan, Lukman; Khoirunnisa; Nazli , Rizal Sjarief Sjaiful (SM Institute, 2025)
This study aims to analyze the effectiveness of gold savings as a financial planning instrument for Hajj in Indonesia, using Bank Syariah Indonesia (BSI) as a case study. A descriptive quantitative approach was employed, utilizing secondary data from internal BSI reports, gold prices, Hajj costs, and the Indonesian Composite Stock Index (IHSG). The results indicate that gold serves as an effective hedge; while Hajj expenses continue to rise annually, the required grams of gold decrease over time, reflecting the assets intrinsic stability and inflation resistance. However, gold savings adoption among BSIs Hajj customers remains low (1.72%), despite significant market potential. Barriers to adoption include limited Islamic financial literacy, insufficient product promotion, and a lack of integration between gold and Hajj savings systems. This study recommends product integration, segmented financial education, and the enhancement of digital features to improve adoption and position gold savings as a strategic, Sharia-compliant tool for Hajj financial planning.